Clopidogrel versus ticagrelor in East Asian patients aged 75 years or older with acute coronary syndrome: observations from the GF-APT registry. (17th November 2022) - Xi, Ziwei; Qiu, Zifeng; Li, Jianan; Qiu, Hong; Guo, Tingting; Wang, Yong; Zheng, Jianfeng; Gao, Yanan; Gao, Runlin
Abstract: The benefits of potent antithrombotic therapy usually come at the expense of a higher risk of bleeding. The efficacy and safety of ticagrelor in elderly East Asian populations remains debated due to the concerns about the imbalance of ischemic and bleeding risks. This study aimed to compare the impact of clopidogrel with ticagrelor on clinical outcomes in East Asian patients aged ≥75 years with acute coronary syndrome (ACS) using data from an institutional registry. We assessed the treatment effect of ticagrelor versus clopidogrel based on propensity scores and multivariate Cox proportional hazards models. A total of 2775 ACS patients were included, of which 235 (8.5%) were treated with ticagrelor. The primary efficacy outcome occurred in 11.9% of patients treated with ticagrelor versus 8.8% treated with clopidogrel. There was no significant association between treatment with ticagrelor and a lower risk of the primary efficacy outcome (p = .156). However, the incidences of all-cause death (hazard ratio [HR] 1.69, 95% confidence interval [CI] 1.02 to 2.79) and major bleeding (adjusted HR 2.20, 95% CI 1.06 to 4.56) were significantly higher in patients treated with ticagrelor than clopidogrel. In elderly patients with ACS from East Asia, the efficacy of clopidogrel was comparable to ticagrelor, while ticagrelor is associated with an increased risk of mortality and major bleeding. Plain Language Summary: What is the context? Current guidelines recommend ticagrelor over clopidogrel for patients with acute coronary syndrome (ACS). There are no specific guidelines concerning the elderly, and data on optimal antiplatelet therapy in elderly are quite scarce. Further study was necessary to identify the efficacy and safety of ticagrelor and clopidogrel in elderly patients from East Asian populations which are reported to be at a higher risk of bleeding. What is new? The risk of major adverse cardiac events did not differ significantly between clopidogrel versus ticagrelor in patients aged ≥75 years from East Asia, while the use of ticagrelor might be associated with increased risk of mortality and major bleeding events. Analyses after propensity score matching showed consistent results on the safety and efficacy of clopidogrel versus ticagrelor. The benefit of potent P2Y12 inhibitor ticagrelor over clopidogrel is questionable in elderly East Asian patients with ACS. What is the impact? This study provides more information on the use of potent antiplatelet therapy in older patients from Asia. The individual assessment of ischemic and bleeding risk is necessary to guide decision-making on DAPT rather than applying the recommendations of guidelines directly.